Effectiveness of Honey Bees Propolis Extract in The Treatment of Type 1 Diabetes Mellitus: Efektifitas Ekstrak propolis Lebah Madu pada Pengobatan Diabetes Tipe 1 - Nisa, Khairun; Kustiawan, Paula M (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Diabetes Mellitus (DM) is a health problem that affects more than 400 million people worldwide. Type 1 diabetes is an autoimmune disease characterized by damage of pancreatic cells followed by hyperglycemia and oxidative stress. Propolis is one of the natural ingredients of bee products. Propolis is known to have bioactive compounds that are rich in flavonoids, phenolic and antioxidant properties so that it has potential as an antidiabetic. Objectives: This writing aims to determine the activity of propolis in test animals of Type 1 DM model. Material and Methods: This research method uses a literature study using type 1 diabetic as inclusion criteria in journal screening. Keywords used include propolis, diabetes and hyperglycemia. Literature is obtained through an electronic data base, such as Google Scholar, PubMed, Scopus and Science Direct. Results: Based on the articles that have been collected, that Type 1 DM causes inflammation which is characterized by decreased immune function due to increased levels of IL-6, IL-1Î² and TNF-Î±. Propolis can reduce levels of pro-inflammatory cytokines, prevent the inflammatory process in diabetes and have hypoglycemic activity. Conclusions: The conclusion of the reviewed article that propolis from honey bee has effectiveness to improve the function of body cells and reduce diabetes complication.